Fractal characteristics of pore structure of hybrid Basalt–Polypropylene fibre-reinforced concrete. (May 2020) - Li, Dan; Niu, Ditao; Fu, Qiang; Luo, Daming
Abstract: The pore characteristics of hybrid basalt–polypropylene fibre-reinforced concrete (HBPRC) are investigated using mercury intrusion porosimetry. The research results indicate that the cumulative pore volume of concrete increases with fibre addition. The pore surface fractal dimension ( D S ) of HBPRC in gel, capillary, and large pore regions decreases sequentially although it has no physical characteristics in a transition pore region. The incorporation of fibres has an insignificant effect on D S in gel and capillary pore regions; however, it has a reducing effect on D S in the large pore region. Furthermore, the greater the concrete strength, the larger D S becomes and the greater the reducing effect of fibres on D S in the large pore region. Through microscopic and mesoscopic analyses, it has been suggested that bubbles introduced by fibres and the weak dispersion of such fibres are the main reasons for the deterioration of the large pore structure of HBPRC.